Mesenchymal stem cell therapy in treatment of erectile dysfunction: Autologous or allogeneic cell sources?. (30th July 2014) - Mangir, Naside; Akbal, Cem; Tarcan, Tufan; Simsek, Ferruh; Turkeri, Levent
<x xml:space="preserve">Abstract</x> Objective To compare the efficacy of intracavernosal injection of autologous and allogeneic mesenchymal stem cells as potential treatment of erectile dysfunction in an experimental rat model. Methods Mesenchymal stem cells were isolated from rat paratesticular fat tissue. Bilateral cavernous nerve injury was carried out followed by immediate intracavernosal injection of either autologous or allogeneic mesenchymal stem cells or mesenchymal stem cell lysates. One month after injection, erectile function was evaluated by means of intracavernosal pressure measurement. All rats were eventually killed, and penile tissues were taken for immunhistochemical and molecular investigation. Results A total of 36 Sprague–Dawley rats were used. The mean maximum intracavernosal pressure in the sham‐operated, autologous and allogeneic mesenchymal stem cell injection groups were significantly better compared with the vehicle injection group (80.5 [3.56], 71.1 [2.9] and 69.2 [3.2] vs 40.33 [4.4], respectively). Mean maximum intracavernosal pressure to mean arterial pressure ratios in the autologous and allogeneic mesenchymal stem cell and mesenchymal stem cell lysate injection groups were not significantly different. Conclusions Intracavernosal injection of both autologous or allogeneic mesenchymal stem cells improve erectile functions in a rat model of cavernous nerve injury. Allogeneic mesenchymal stem cells might provide clinicians with ready to use, standardized and, in certain cases, more effective products. More studies focusing on long‐term immunological aspects of allogeneic mesenchymal stem cells are required.